A methodology for the assessment of the effect of climate change on the thermal-strain–stress behaviour of structures. (1st June 2015) - Santillán, D.; Salete, E.; Toledo, M.Á.
Highlights: A methodology for assessing the effects of climate change on structures is proposed. The impacts of climate change on the structural behaviour of an arch dam are analysed. Concrete temperature is expected to increase from 2.5 to 5.6 K. Mean radial displacements to increase in some cases even more than 148%. Some adaptation strategies are outlined. Abstract: Thermal loads can cause significant stresses in some structures such as bridges or arch dams. Studies in arch dams show that thermal loads have the most significant effect for causing cracking than other service loads. Moreover, since researches on climate change announce that mean temperature on Earth is expected to increase, the assessment of the impact of the future temperature increase on the structural behaviour of sensitive infrastructures should be considered. This paper proposes a methodology for the assessment of the impacts of global warming on the structural behaviour of infrastructures. The paper links future climate scenarios to the thermal, stress and displacement fields of the structure. The methodology is illustrated with a case study: La Baells arch-dam. The expected stress and displacement fields of the dam under several future climatic scenarios were computed by finite element models. Concrete temperature are expected to increase up to 5.6 K, which will make annual average radial displacements increase in some cases even more than 100%. Tensile stresses are also projected to change and should be adequately monitored in the future. Finally, several adaptation strategies are outlined.